An early role for zebrafish hoxd4a and its cofactors in hematopoiesis - Zhang, Changqing (2017)
In contrast to a more expected role of Hox genes during gastrulation, knockdown of hoxd4a results in decreased expression of the hemangioblast maker scl and subsequent defects in hematopoiesis. To confirm an early role for hoxd4a, we engineered inducible Hoxd4a activity by fusion to the ligand binding domain of a human estrogen receptor variant. We further tested the importance of DNA binding and interaction with PBX cofactors through the use of appropriate Hoxd4a mutants. A synthetic genetic interaction approach was employed to assess its cooperation with BMP signaling. Our findings confirm a novel pre-gastrulation function for hoxd4a in controlling zebrafish primitive hematopoiesis that is dependent on its cofactors. Additionally, we showed that while hoxd4a null mutants fail to recapitulate morphant phenotypes, they are less sensitive to the effect of anti-hoxd4a morpholino injection, indicating that the knockdown phenotype is specific, but loss of hoxd4a function is compensated in genetic mutants.